Effects of soil moisture and an AC-electric field on the phytoremediation of the Cd-contaminated soil - Hu, Juanxin (Environmental technology, 2024)
Phytoremediation enhanced by electric field has been considered a green and low-cost technology for remediating heavy metal-contaminated soils. Soil moisture is a main environmental factor that affects Cd availability in the soil. However, the effects of soil moisture and AC-electric field on the remediation efficiency of willow (Salix spp.) and S. Alfredii interplanted together remain unclear. In the present study, we designed four treatments (60% soil field capacity, 60% soil field capacity + 0.5 V·cm-1 AC, 100% soil field capacity, 100% soil field capacity + 0.5 V·cm-1 AC) to explore the impacts of soil moisture and AC-electric field on soil Cd availability and Cd accumulation in plants. The results showed that the application of an AC-electric field significantly increased soil Cd availability by 20.9% and 10.8% under both 60% and 100% soil field capacity, respectively. Both high water with and without AC-electric field treatments reduced the proportion of acid-extractable and reducible Cd of soil but increased the proportion of residual Cd. Compared with the control, an AC-electric field with 60% soil field capacity significantly enhanced the biomass of S. Alfredii shoots by 31.2% and increased Cd accumulation in willow leaves and S. Alfredii shoots by 14.6% and 32.3%, respectively. In addition, the biomass production of willow was significantly enhanced but the uptake of Cd by willow was dramatically decreased under an AC-electric field with high water treatment. Therefore, these results suggest that the AC-electric field combined with 60% soil field capacity may be a more promising remediation technique to clean up the Cd-contaminated soil